Faculty Senate Minutes, November 19, 2015 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2015)
Valdosta State University Faculty Senate. "Faculty Senate Minutes, November 19, 2015." (Valdosta State University, 2014).
Keywords: Corporate minutes; Faculty Senate; Valdosta State University